Inequality in breast cancer: Global statistics from 2022 to 2050 - Ling Liao (Breast)
This study evaluates the global inequalities of breast cancer incidence and mortality from 2022 to 2050 with the latest GLOBOCAN estimates. It focuses on disparities across continents, age groups and Human Development Index (HDI) levels. In 2022, Africa shows the highest positive slope values of age-standardized rates (world) of mortality vs. incidence, both for those under 40 (0.346) and those 40 and older (0.335). These values contrast with those for Asia (0.085, 0.208), Europe (0.002, −0.014), Latin America and the Caribbean (0.17, 0.303), Northern America (−0.078, −0.188), and Oceania (0.166, −0.001). In both age groups, lower HDI levels are correlated with higher slope values and vice versa. Projections to 2050 indicate significant increases in the burden of breast cancer, with persistent yet varied disparities and differences. This highlights the need for differentiated strategies in breast cancer prevention, early-stage diagnosis, and treatment.